Perceived and functional parental health literacy and vaccine hesitancy among Cypriot parents - Menikou, Joanna; Middleton, Nicos; Papastavrou, Evridiki; Nicolaou, Christiana (My University, 2023)
Background Assessing the association of perceived health literacy (PHL) and functional health literacy (FHL) with childhood vaccination hesitancy (VH) among parents is important in the context of developing targeted responses given that VH is of increasing public health concern. Methods A cross-sectional study was conducted with a convenience sample of parents of children, aged 6 months to 15 years old, presenting in pediatric primary care centers across 3 Cypriot cities. Participants responded to the HLS-EU-Q47 and the NVS (Newest Vital Sign), a self-rated and performance-based tool of health literacy (HL), respectively. They also completed a questionnaire tapping on attitudes and practices regarding childhood vaccinations. Parents were classified according to the overall and domain-specific PHL and FHL, and associations with VH were explored. Results Amongst 207 parents (82.6% female, 86.0% tertiary education), higher PHL was associated with certain positive attitudes and practices related to childhood vaccination e.g. childhood vaccination according to health science, whereas higher FHL appeared to be associated with certain negative attitudes and practices e.g. more concerns about side effects of vaccines. Lack of accurate information was the only reported vaccination barrier associated with lower PHL (34.28, SD = 7.54 versus 36.51, SD = 7.20 p = 0.04), whereas no vaccination barrier was associated with FHL. No significant associations between PHL and VH were observed. In contrast, higher FHL was associated with VH (p = 0.01) with parents categorized as ‘refusers’ (3.67, SD = 2.64) or ‘hesitant acceptors’ (3.15, SD = 2.74) having higher FHL than parents categorized as ‘delayers’ (2.95, SD = 2.63) or ‘non-hesitant acceptors’ (2.99, SD = 2.42). Conclusions Assessing both PHL and FHL led to a more comprehensive understanding on the influence of parental HL towards childhood vaccination which can guide the design and implementation of interventions to address VH among parents. Key messages • While parental HL is associated with childhood VH, a mixed pattern emerged depending on whether HL was operationalized using a perceived or functional measure. • While health education at clinical and population level are needed to counteract parental VH, the association of parental HL with childhood vaccination attitudes and practices is not straightforward.